FAKTOR LINGKUNGAN KELUARGA YANG MEMPENGARUHI ADAPTASI REMAJA DI KELURAHAN BINUANG KAMPUNG DALAM KECAMATAN PAUH KOTA PADANG - Yuli Mardina (Universitas PGRI SUMATERA BARAT, 2019)
This research is motivated by adolescents who are less adaptable in the environment. the purpose of this study was to describe: family environmental factors that affect adolescent adaptation seen from 1) family atmosphere, 2) family socioeconomic conditions, 3) adolescent position in the family, 4) gender differences. This research is qualitative research. Key informants were teenagers with the initials EG and GP and four additional informants consisting of FS (FG parents), SP (EG's older sister), NV (WOMAN's older sister GP), and MK (GP's younger sister). The research instrument used in this study was an interview. data analysis techniques used through data reduction, data presentation, and data interpretation. The results of the study revealed that family environmental factors that affect adolescent adaptation seen from 1) family atmosphere that is not harmonious with family members causes children to be difficult to adapt; 2) the economic condition of the family starts from the middle to lower so that adolescents are not confident properly; 3) the position of adolescents as the firstborn/only child at home so that adolescents have a sense of responsibility to protect family members; 4) gender differences in men/women, in adapting to different environments men are faster in conducting socialization with the community, whereas women take a little longer to socialize with their environment. based on the results of this study it is recommended for adolescents to be able to adapt to the environment and the environment in which adolescents live.